POLA PENATAAN RUANG UNIT PEKARANGAN DI DESA BONGLI TABANAN - Adhika, I Made (Jurnal Natah; Vol. 2, No. 1 Februari 2004, 2012)
Spatial structure of yard element in Bali commonly is founded on Tri Angga and Sanga Mandala Concept as well that is explicated into a form of an open space in center that is called “natah”. In fact, it seemly faces the other patterns, which are its special and unique by regarding the local values as would be reviewed in this paper. The encoding is derived from direct observation in field and conducting interview to the community stakeholders as well and followed by analyzing the existing spatial structure pattern and its changes. Refer to the analizing completed, is obtained that the spatial structure pattern of yard unit in Bongli Village is not derived from Sanga Mandala Consept but based on the value structure that founded on the height/level as main value. The other is attained that it have occurred the change of the spatial structure of yard unit because of the exchange of kitchen building unit.
Keywords: spatial structure pattern, sanga mandala, value pattern and yard.